The role of stock market volatility in predicting macroeconomic quantities. - Leong, Florence Mei Hua. (2013)
This paper explores predictability of stock market volatility over macroeconomic quantities. We measure stock market volatility with the variance of stock prices while the macroeconomic quantities are represented by the growth rates of macroeconomic variables. This paper performs correlation analyses and multivariate linear regressions of four different volatility measures – average systematic volatility, average idiosyncratic volatility, average total volatility and aggregate market volatility, on five chosen United States macroeconomic variables. The five variables are real gross domestic product, employment rate, industrial production index, real personal consumption expenditure and nondurables goods & services consumption.